ESTIMATING THE MOVEMENT OF BELEX15 INDEX VALUES USING THE ARIMA MODEL - Petrović, Marijana (Journal of process management and new technologies, 2020)
In this paper the author tried to find a suitable model for forecasting the movement of the Belex15 index on the Belgrade Stock Exchange, using one of the most used methodologies of the last decades - the ARIMA method. Through method application in four steps, the author has come to the conclusion that ARIMA (0,1,11) is the optimal model for forecasting, using the given stock index data series. After evaluating the statistical appropriateness of the model and its application to short-term forecasts, the results were compared with the results of the previous work of the author in which he made the forecast using the linear and nonlinear methods (linear regression and neural networks) to the same data. The selected ARIMA model showed good statistical suitability and the possibility of a satisfactory short-term forecast of the Belgrade Stock Exchange index, although it showed a higher RMSE (root mean square error) compared to the nonlinear model applied to the same data.
Keywords: ARIMA; Belex15